Effectiveness of information services with the SGD(Small Group Discusion) approach to improve students' learning independence - Ramadhan, Muhammad Fiqri; Harahap, Ade Chita Putri (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
The purpose of this study was to see the effectiveness of information services with the SGD (Small Group Discussion) approach in improving students' learning independence. Learning independence is a way for individuals to improve ideas, emotions, strategies, and actions that are directed at achieving learning goals. The researcher used a quantitative approach with a pre-experimental research type, which applied a one group pretest posttest design. The population was all BKPI students with a total of 120 students, the sample obtained was 30 students who had low learning independence conditions. The sample selected in this study used non-probability sampling, especially with the purposive sampling technique. Data collection used a learning independence scale. The paired sample t-test is a data analysis technique used with the help of SPSS version 22, with a significance level of α = 0.05. Based on the data obtained, the sig value (2-tailed) was 0.000 <0.05. So it can be concluded that Ho is rejected and Ha is accepted, so information services are effective with the SGD (Small Group Discussion) approach to increasing students' learning independence.